2021
DOI: 10.1101/2021.01.22.427329
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implant- and anesthesia-related factors affecting threshold intensities for vagus nerve stimulation

Abstract: Vagus nerve stimulation (VNS) is used as therapy in epilepsy and depression and is tested as a potential treatment for several chronic disorders. Typically, VNS is delivered at increasing stimulus intensity until a response is observed (threshold intensity). Factors that affect threshold intensities for engagement of different fiber types and concomitant physiological responses have not been studied. We determined neural and physiological responses to increasing stimulus intensities of VNS in anesthetized and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Once the rats were under anesthesia, they were placed in a supine position, and hairs were removed using clippers and depilatory cream. The neck area was then cleaned using an aseptic technique, as described before ( 49 ). 1-2 cm horizontal skin incision was given on the neck, and salivary glands were separated.…”
Section: Methodsmentioning
confidence: 99%
“…Once the rats were under anesthesia, they were placed in a supine position, and hairs were removed using clippers and depilatory cream. The neck area was then cleaned using an aseptic technique, as described before ( 49 ). 1-2 cm horizontal skin incision was given on the neck, and salivary glands were separated.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, vagus nerve stimulation (VNS) has been considered to be a promising therapeutic approach to treat diverse pathological conditions, such as epilepsy 5-8 , depression 9 , and cardiac diseases 10-14 by restoring the vagal tone to a physiological level.In cardiac medicine, VNS has proven to promote cardioprotective and anti-fibrillatory effects, thus providing a promising therapeutic approach for non-pharmacological treatment of various cardiac pathological conditions, such as ventricular arrhythmias 15 , atrial fibrillation 13 and heart failure 16,17 . However, the fact that VNS is mostly applied to the cervical level due to surgical ease of access and the possibility to target various organ-related fibers, it is often accompanied by difficultly controllable systemic off-target effects [18][19][20] .Although numerous studies have explored diverse effects of VNS on HR and hemodynamic function, invivo 11,[21][22][23][24] and in-situ 10,[25][26][27] , including anti-antiarrhythmic 15 and cardioprotective effects 28 , or alleviation of hypertension 29 , the outcomes are diverse, and the impact of VNS on the cardiac activity is still not fully understood. One main hindrance to better understand the cardiac effects of VNS is the presence of autonomic reflexes in-vivo, anesthetic and analgesic effects, and inter-individual variations.Addressing this problem, the purpose of this study was to establish a novel model of vagally innervated and fully isolated rabbit heart in order to study the cardiac effects of ex-vivo VNS under well-controllable und reproducible experimental conditions.…”
mentioning
confidence: 99%
“…Although numerous studies have explored diverse effects of VNS on HR and hemodynamic function, invivo 11,[21][22][23][24] and in-situ 10,[25][26][27] , including anti-antiarrhythmic 15 and cardioprotective effects 28 , or alleviation of hypertension 29 , the outcomes are diverse, and the impact of VNS on the cardiac activity is still not fully understood. One main hindrance to better understand the cardiac effects of VNS is the presence of autonomic reflexes in-vivo, anesthetic and analgesic effects, and inter-individual variations.…”
mentioning
confidence: 99%
“…Isoflurane anesthesia is commonly used in vagus and carotid sinus nerve stimulation studies 90 . Even though is does not alter direct electrical activation of vagus fibers 83 , it has been recently shown that it significantly increases physiological threshold intensities of VNS 57 . Anesthesia used in our study likely impacts synaptic transmission at the vagal ganglia and blunts baroreflex mediated cardiac responses, even though baroreceptor activation-induced heart rate changes are still observed at high isoflurane concentrations 91 .…”
Section: Discussionmentioning
confidence: 98%
“…This is possibly related to the proximity between the targeted fiber and the stimulating electrode and is critically dependent on the robustness of the neural interface. As a result, waveform manipulations may be less attractive in therapies relying on long-term implants, which generally show longitudinal changes in stimulation effectiveness 56,57 , or when scaling to larger diameter, more complex nerves in large animal models or humans, where there is more anatomical variability in the nerve-electrode interface 58 .…”
Section: Discussionmentioning
confidence: 99%